Pregnancy in a caesarean scar: case report - Pantigoso-Gutierrez , Digna (2025)
Cesarean scar pregnancy is occurring more frequently due to the worldwide increase in cesarean sections. It is a rare ectopic pregnancy associated with potentially serious complications. The objective was to raise awareness about cesarean scar pregnancy (CSP) in a public hospital in Lima, Peru. A 34-year-old woman with G4: P3013, 7 weeks of amenorrhea, had an obstetric history of three cesarean sections and one miscarriage. Transvaginal ultrasound revealed a gestational sac with a yolk sac and no embryo attached to the cesarean scar, protruding into the bladder, thinned residual myometrium, and vascularization around the gestational sac. This met the diagnostic criteria for CSP Type I. Initial treatment was medical, followed by a planned laparoscopic hysterectomy. It is concluded that CSP can be asymptomatic and requires diagnosis and appropriate treatment early in the first trimester. There is no consensus on optimal management; each case must be individualized.